Impactos regionais de choques de produtividade e reduç\~ao de desigualdades: O caso de Regi\~ao Nordeste - Carlos Wagner de Albuquerque Oliveira; Bruno de Oliveira Cruz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper analyzes regional impacts of different policies choices on the long-run trend, especially in the Northeast. Simulations, in the four different scenarios, ranges from 2015-2030, using the International Futures (IFs) model. This model encompasses a huge number of historical data for 186 countries. Thus, it is possible to simulate global change and the impact of policies changes in different countries. Themain results are the following. 1)There was a clear problem in terms of gross domestic product (GDP) growth for Brazil and Latin America, both were the regions with the lowest rate of GDP per capita growth and Brazil had an even lower growth than Latin America. 2) Productivity shock might have an impact in the Brazilian growth, comparing to the scenario base the rate of GDP per capita goes from 0.61 to 1.24. As one combines productivity shocks with inequality reduction, the Brazilian growth rate goes to 1.42. 3) In regional terms, even if Northeast still grows at a higher rate than National GDP, there is not significant change in the dynamics of convergence, even if the most favorable, the beta-convergence coefficient keeps at the same low level of 0,06. None of the Northeast states are able to reach 75% of the National GDP at the end of 2030. 4) In both scenarios that deals with inequality reduction, poverty rate is substantially reduced, however none of the Northeast states is able to vanish poverty in 2030. 5) Decomposing the poverty reduction, one can show that GDP growth explains 35% in the Northeast, while inequality reduction is responsible for 56%. In short, the results show that productivity shocks and reduction in income inequality without any regional bias is not able to reduce regional inequalities in the 2030, before the pandemic crises.
Keywords: R11; R13; R15; 330; productivity shocks; income inequality reduction; regional simulation